PROCEDURES IN ENGLISH-VIETNAMESE TRANSLATION OF MOVIE TITLES ON TELEVISION = Phương thức chuyển ngữ tên phim Anh-Việt trên truyền hình - Nguyễn, Thị Thùy Ngân (2020)
Under the vast influence of economic development, film industry in Vietnam has been strengthened significantly. Thus, the more movies are imported into Vietnamese market, the more translation is needed in terms of both titles and subtitles. This paper focuses on studying the procedures used to translate English movie titles shown on television. The thesis consists of five chapters. Chapter I plays the function of an introductory part providing readers with background and organization of the research. The next chapter presents background knowledge about translation as well as movie title translation. The methodology to do the research is found at Chapter III. The last two chapters play most important parts of the whole research because they provide major findings of the research, about the most common procedures used in such brief and succinct movie titles. For instance, English nominal titles are frequently translated with literal procedure while proper noun titles mostly employ transference. Besides, the reserch also gives recommendations on movie title translation as well as points out limitation of the current studies and suggestion for further ones.